Can climate change enhance biology lessons? A quasi-experiment. Issue 2 (2nd April 2016) - Monroe, Martha C.; Hall, Stephanie; Li, Christine Jie
ABSTRACT: Climate change is a highly charged topic that some adults prefer to ignore. If the same holds true for secondary students, teachers could be challenged to teach about climate change. We structured one activity about the biological concepts of carbon cycle and carbon sequestration in two ways: with and without mention of climate change. Results suggested that students ( n = 22) who learned about carbon in the context of climate change made significant improvements in their knowledge of the carbon cycle and sequestration over those ( n = 24) who learned about carbon without mention of climate change. Interest in climate change may increase learning.